Pengaruh Teknologi Informasi, Pengendalian Internal, Whistleblowing System, Dan Anti-Fraud Awareness Terhadap Pencegahan Fraud (Studi Kasus Pada PT. Hexa Daya Solusi) - Gishella Avillia Wiguna; Sofie Sofie (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This study aims to examine the influence of information technology, internal controls, whistleblowing systems, and anti-fraud awareness on fraud prevention at PT. Hexa Daya Solusi. This research was conducted using quantitative methods. The data used in this research is primary data. The population used in this study are employees who use Accurate Online at PT. Hexa Daya Solusi in 2023. A total of 30 respondents were selected using the purposive sampling method. The analysis technique in this study is multiple linear regression analysis. The results of the hypothesis testing in this study indicate that information technology and the whistleblowing system have a positive and significant influence on fraud prevention. Meanwhile, internal control and anti-fraud awareness has a negative and insignificant effect on fraud prevention.